Validated spectrophotometric methods for determination of certain aminoglycosides in pharmaceutical formulations - Mahmoud A. Omar, Dalia M. Nagy, Mohamed A. Hammad, Alshymaa A. Aly (Journal of Applied Pharmaceutical Science, 2013)
Two simple and selective spectrophotometric methods have been proposed for the determination of amikacin sulfate, gentamicin sulfate, kanamycin sulfate, streptomycin sulfate, neomycin sulfate and tobramycin in pure forms and in their pharmaceutical formulations. Both methods are based on the proton transfer from the Lewis acid such as 2,4,6-trinitrophenol (picric acid; PA) or 2,4-dinitrophenol (2,4-DNP) to the primary amino group of aminoglycosides as Lewis base with formation of yellow ion-pair complexes. Different variables and parameters affecting the reactions were studied and optimized. Beer’s plots were obeyed in a general concentration range of 2.5-140 and 2.5–100 µg mL-1 with 2,4-DNP and PA, respectively, with correlation coefficients not less than 0.9991. The proposed methods were successfully applied to the analysis of the cited drugs in their dosage forms. The proposed methods were validated according to ICH and USP guidelines with respect to specificity, linearity, accuracy, precision, robustness and ruggedness.
Keywords: Aminoglycosides, 2,4-dinitrophenol, picric acid, spe